MaqaṢid Syari`ah Pembagian Harta Warisan Bagi Wanita - Millah, Ainul, DR. Syamsul Hidayat, M.Ag, Dr. Imron Rosyadi M.Ag (2016)
In the pre-Islamic period (jahiliyah), there is no share for women from what is left by parents and those nearest related. After that, Islam came. It changed the pre- Islamic period tradition by obtaining the right for women to receive the share of inheritance that was decided by Allah and His Messenger in the Holy Qur'an and The Sunnah. Nowadays, the feminist activists are struggling for the equality to men on all cases included inheritance distribution. They think Islam discriminates the women because it obtains the lower portion of inheritance than the men. Those cases attracted the writer to conduct this research. The aims of this research are (1) to know the MAQAṢID SYARI`AH (the objective of particular provision, law and text to realize in human life) Islamic inheritance distribution for the women, (2) to know the Islamic inheritance distribution for women by ta'shib and fardh law and (3) to identify why the women do not always receive the lower portion of inheritance than the men because the women could get the equal portion to the men. Indeed, in certain case the women could receive the inheritance but the men couldn't. This research belongs to qualitative and bibliographic research. Therefore, it is library research by using historic-philosophic approach. The data will be analyzed serially and interactionally by three steps. Those steps are (1) data reduction, (2) data presentation and (3) data verification. The research results show that there are 10 women who receive the share of inheritance. They are: mother, grandmother (mother to a father), grandmother (mother to a mother), daughter, grandniece (daughter to a son), female sibling of the same parents, female sibling of the same father, female sibling of the same mother, wife and the women that freed the slave. The women receive the share of inheritance through ta'shib (certain distribution) and fardh (uncertain distribution) law. The women receive the share of inheritance if there is a male whose belongs to inherited. Yet, the women receive the share of inheritance through far' law if there is no male whose belongs to inherited. The inheritance distribution through fardh law obtains more benefit to the women rather than ta'shib law because sometimes the women receive more portion that the men, but sometimes they could receive lower portion. Indeed, they don't receive the share because the inheritance has been divided to the other inherited through fardh law. The women do not always receive the lower portion of inheritance than the men. In certain condition they could receive equal portion to the men. The example is the position of parents (mother and father) with the son; they receive the same portion a sixth share of inheritance if the decease did not leave father and son. In certain condition too, the women could receive the share of inheritance, but the men couldn't. The example is when female sibling of the same father receives the share of inheritance through fardh law if there is no male sibling of the same father, but the women could not receive it if there is male sibling that receives it through ashobah ma'al ghoir law because the whole inheritence has been divided to ashabul furudh.